Impact of Fluoroquinolones on Tendon Health: A Comprehensive Overview for the General Population and Athletes - Kucharczyk, Emilia; Kucharczyk, Natalia; Pawłuszkiewicz, Karolina (Quality in Sport, 2024)
Introduction: Fluoroquinolones are a class of broad-spectrum antibiotics widely used to treat various bacterial infections. Despite their effectiveness, increasing evidence links fluoroquinolones to tendinopathy and tendon rupture, with cases occurring shortly after initiation or even months post-therapy. This review provides a comprehensive overview of the impact of fluoroquinolones on tendon health - highlighting the underlying pathomechanisms, clinical manifestations, and epidemiology of fluoroquinolone-associated tendinopathy. Purpose of the work: The purpose of this study is to review the effects of fluoroquinolones on tendon health in the general population. Special attention is given to the athletes, who are particularly vulnerable to tendon injuries. Materials and methods: A comprehensive analysis of research articles available on PubMed, Google Scholar, Web of Science, Embase, and Scopus was conducted using search terms related to: "fluoroquinolones," "tendinopathy," "tendon rupture," "athletes" and "connective tissue damage." Results: Fluoroquinolones are linked to an increased risk of tendinopathy and tendon rupture, particularly among those with certain risk factors, including athletes. Understanding the mechanisms by which fluoroquinolones affect tendon tissue and recognizing early signs of tendon damage can help mitigate these risks. Prevention strategies, including cautious prescribing fluoroquinolones and targeted rehabilitation programmes, may reduce the adverse effects of fluoroquinolone usage, particularly in high-risk groups like athletes.